Porous defective carbon ferrite for adsorption and photocatalysis toward nitrogen compounds in pre-treated biogas slurry - Li, Jie (Scientific reports, 2022)
Carbon ferrite (C-Fe 3 O 4 ) with hydrophilic functional groups and lattice defects was synthesized in anhydrous molten alkali system by fern leaves and ferric chloride as raw materials. Structural characterization results showed that carbon ferrite obtained oxygen-containing groups on the carbon surface. And structural pores and lattice defects resulted from spontaneous accumulation and “directive-connection” of ferrite (Fe 3 O 4 ) nanoparticles. Carbon ferrite displayed an adsorption efficiency of 29.0% and excellent photocatalytic degradation of 80.8% toward nitrogen compounds (initial concentration of 430 mg/L) in pre-treated biogas slurry. The micromechanism for nitrogen compounds removal was discussed at the molecular/atomic level by exploring carbon ferrite “structure-activity”, which provides a design idea from microscopic perspective for the preparation of environmental materials with reactive sites.